Preschoolers’ Novel Noun Extensions: Shape in Spite of Knowing Better - Saalbach, Henrik; Schalk, Lennart (Frontiers in Psychology, 2011)
We examined the puzzling research findings that when extending novel nouns, preschoolers rely on shape similarity (rather than categorical relations) while in other task contexts (e.g., property induction) they rely on categorical relations. Taking into account research on children’s word learning, categorization, and inductive inference we assume that preschoolers have both a shape-based and a category-based word extension strategy available and can switch between these two depending on which information is easily available. To this end, we tested preschoolers on two versions of a novel-noun label extension task. First, we paralleled the standard extension task commonly used by previous research. In this case, as expected, preschoolers predominantly selected same-shape items. Second, we supported preschoolers’ retrieval of item-related information from memory by asking them simple questions about each item prior to the label extension task. Here, they switched to a category-based strategy, thus, predominantly selecting same-category items. Finally, we revealed that this shape-to-category shift is specific to the word learning context as we did not find it in a non-lexical classification task. These findings support our assumption that preschoolers’ decision about word extension change in accordance with the availability of information (from task context or by memory retrieval). We conclude by suggesting that preschoolers’ noun extensions can be conceptualized within the framework of heuristic decision making. This provides an ecologically plausible processing account with respect to which information is selected and how this information is integrated to act as a guideline for decision-making when novel words have to be generalized.